Digitale Schriftmedien - Eine Melange aus Informationsgut und Software - Svenja Hagenhoff (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2014)
– Since the introduction of mobile devices as smartphones, tablets or specific e-book readers, the print industry offers its products, such as books, newspapers and magazines, more and more of¬ten in digital form. While the original products were characterized by paper and its physical features, the digital goods have partially dif¬ferent properties. On the one hand, the properties affect the producers of the media who have to make decisions regarding the product design. On the other hand, the user or reader of the media is affected: The manifestations of the properties of a medium can be particularly useful or they need getting used to. They can also hinder the use or reception of a medium. Digital written media are construed to as products which inherit the properties of two parent goods. One the one hand there are information goods, on the other there is software. A product can be de¬signed in a well-advised manner only if its properties and their mani¬festations are known. Therefore, the aim of this paper is to identify and to describe the specific characteristics of digital written media to demonstrate design possibilities and necessities.
urn:nbn:de:bvb:29-opus4-55699
Keywords: 020; Bereitstellungsqualität; Digitale Schriftmedien; Gebrauchstauglichkeit; Informationsgut; Medienwirtschaft; Mensch-Maschine-Schnittstelle; Software; Typografie; Usability; Mediensektor; Digitale Medien; Benutzerfreundlichkeit